2017
DOI: 10.1002/jbm.a.36304
|View full text |Cite
|
Sign up to set email alerts
|

Increased affinity of endothelial cells to NiTi using ultraviolet irradiation: An in vitro study

Abstract: Nickel-titanium alloy (NiTi) is one of the most popular materials used endovascularly because of its shape memory and superelasticity. The NiTi device needs to be covered by endothelial cells after being placed in the blood vessel to reduce ischemic complications. The objective of this study was to examine the impact of ultraviolet (UV) irradiation on the biocompatibility of NiTi surfaces with endothelial cells. NiTi sheets were treated with UV irradiation for 48 h and human aorta derived endothelial cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Similarly, hydrophilic zirconia and Co-Cr alloy enhances the initial behavior and response of osteoblasts compared to hydrophobic zirconia and Co-Cr alloy, respectively [41,[43][44][45][46]. Hydrophilic titanium also effectively attracts and retains proteins and other cell types such as endothelial cells [47,48]. There are few reports of the effect of hydrophilicity/hydrophobicity of resinous materials.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hydrophilic zirconia and Co-Cr alloy enhances the initial behavior and response of osteoblasts compared to hydrophobic zirconia and Co-Cr alloy, respectively [41,[43][44][45][46]. Hydrophilic titanium also effectively attracts and retains proteins and other cell types such as endothelial cells [47,48]. There are few reports of the effect of hydrophilicity/hydrophobicity of resinous materials.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such surface texture-induced microenvironments with stagnated and concentrated blood and proteins may explain the successful, contact osteogenesis or osseointegration. The effects of hydrophilic titanium surfaces on the recruitment of blood, proteins, and cells have been reported extensively [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The present study has revealed that a similar effect can occur by surface texturing.…”
Section: Discussionmentioning
confidence: 99%
“…We validated the appearance of a hydrophilic surface on Grade 4 implants and titanium disks because the majority of implants are constructed from grade 4 titanium [90,93]. The effect of UV treatment, such as the conversion to a hydrophilic surface, has been demonstrated for various surface types and materials, including type 2 commercially pure titanium, grade 5 titanium alloy, and zirconia [29,31,38,41,42,46,47,49,50,55,63,64,66,69,72,[95][96][97].…”
Section: Discussionmentioning
confidence: 99%